Average plasma sheet polytropic index as observed by THEMIS - D. Frühauff; J. Z. D. Mieth; K.-H. Glassmeier (Annales Geophysicae, 2017)
Multi-spacecraft data from the years 2008 to 2015 of the THEMIS mission particularly in the near-Earth plasma sheet are used in order to empirically determine the polytropic index in the quiet and active time magnetotail. The results of a number of previous studies in the 1990s can be confirmed. An analysis of the total database, although showing poor correlation, results in an average polytropic index of γ = 1. 72. The active time plasma sheet is well correlated with an average γ = 1. 49. However, the data scattering suggests that the analysis of the data in total is not adequate. In order to reduce the timescales, individual spacecraft orbits are analyzed, giving a broad distribution of polytropic indices throughout the plasma sheet. The major part of the distribution falls in a range between γ = 0. 67 and γ = 2. Our results indicate a variety of thermodynamic processes in the magnetotail and an all-time presence of heat exchange of the plasma. A description of the plasma sheet using an equation of state with a single γ is probably inadequate. This necessitates the application of more sophisticated approaches, such as a parametrization of the heat flux vector in magnetohydrodynamic equations or a superposition of polytropic indices.